Synergistic protection by isoquercitrin and quercetin against glutamate-induced oxidative cell death in ht22 cells via activating nrf2 and ho-1 signaling pathway: Neuroprotective principles and mechanisms of dendropanax morbifera leaves - Park, Hye Jin; Kim, Ha Neul; Kim, Chul Young; Seo, Min Duk; Baek, Seung Hoon (Antioxidants, 2021)
Dendropanax morbifera leaves (DML) have long been used as traditional medicine to treat diverse symptoms in Korea. Ethyl acetate-soluble extracts of DML (DMLE) rescued HT22 mouse hippocampal neuronal cells from glutamate (Glu)-induced oxidative cell death; however, the protective compounds and mechanisms remain unknown. Here, we aimed to identify the neuroprotective ingredients and mechanisms of DMLE in the Glu-HT22 cell model. Five antioxidant compounds were isolated from DMLE and characterized as chlorogenic acid, hyperoside, isoquercitrin, quercetin, and rutin by spectroscopic methods. Isoquercitrin and quercetin significantly inhibited Glu-induced ox-idative cell death by restoring intracellular reactive oxygen species (ROS) levels and mitochondrial superoxide generation, Ca2+ dysregulation, mitochondrial dysfunction, and nuclear translocation of apoptosis-inducing factor. These two compounds significantly increased the expression levels of nuclear factor erythroid-2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) in the presence or absence of Glu treatment. Combinatorial treatment of the five compounds based on the equivalent concentrations in DMLE showed that significant protection was found only in the cells cotreated with isoquercitrin and quercetin, both of whom showed prominent synergism, as assessed by drug–drug interaction analysis. These findings suggest that isoquercitrin and quercetin are the active principles representing the protective effects of DMLE, and these effects were mediated by the Nrf2/HO-1 pathway.
Keywords: Dendropanax morbifera leaves; Glutamate-induced oxidative cell death; Heme oxygenase-1; Isoquercitrin; Nuclear factor erythroid 2-related factor 2; Quercetin; Synergism